Effect of Reduced Rates of N, P and K on the Yield of Rice (Oryza sativa L.) and its Nutrient Uptake - Hasan, ABM Masud; Rahman, Md Mizanur; Hashem, MA (The Agriculturists, 2010)
An experiment was conducted to study the yield response and nutrient uptake of rice (BRRI dhan30) to reduced rates of N, P and K from the recommended fertilizer doses (RFD). The experiment was laid out in a randomized complete block design with four replicates. There were ten treatments viz. T1 (control), T2 (RFD), T3 (RFD - 20% N), T4 (RFD - 40% N), T5 (RFD - 20% P), T6 (FRD - 40% P), T7 (RFD - 20% K), T8 (RFD - 40% K), T9 (RFD - 20% NPK) and T10 (RFD - 40% NPK). The recommended fertilizer doses of the crop were 100 kg N, 20 kg P, 40 kg K, 20 kg S and 3 kg Zn ha-1. The highest grain yield (5.10 t ha-1) and straw yield (7.02 t ha-1) were obtained by applying recommended doses of fertilizers which were insignificantly different from those observed in the treatments where N, P and K were reduced at the rate of 20% from the recommended doses. Similar results were also found in case of P, K and S content and uptake by rice plant, while the variation for N was found significant. Overall results indicated that 20% reduction of either N or P or K from the recommended doses would not significantly affect the yield of rice.